Buyer–Supplier Relationships and the Stakeholder Theory of Capital Structure - BANERJEE, SHANTANU; DASGUPTA, SUDIPTO; KIM, YUNGSAN (Journal of Finance, 2008)
ABSTRACT Firms in bilateral relationships are likely to produce or procure unique products—especially when they are in durable goods industries. Consistent with the arguments of Titman and Titman and Wessels, such firms are likely to maintain lower leverage. We compile a database of firms' principal customers (those that account for at least 10% of sales or are otherwise considered important for business) from the Business Information File of Compustat and find results consistent with the predictions of this theory.